2017
DOI: 10.1016/j.physrep.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Ranking in evolving complex networks

Abstract: Complex networks have emerged as a simple yet powerful framework to represent and analyze a wide range of complex systems. The problem of ranking the nodes and the edges in complex networks is critical for a broad range of real-world problems because it affects how we access online information and products, how success and talent are evaluated in human activities, and how scarce resources are allocated by companies and policymakers, among others. This calls for a deep understanding of how existing ranking algo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
170
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 223 publications
(178 citation statements)
references
References 330 publications
(711 reference statements)
3
170
0
5
Order By: Relevance
“…State-of-the-art similarity evaluation methods could be utilized to carry out link prediction, including common neighbors (CN), Jaccard index (JB), resource allocation index (RA), local path index (LP), and structural perturbation method (SPM) (see the part of Baseline and [38]). …”
Section: Network Formation and Metricsmentioning
confidence: 99%
“…State-of-the-art similarity evaluation methods could be utilized to carry out link prediction, including common neighbors (CN), Jaccard index (JB), resource allocation index (RA), local path index (LP), and structural perturbation method (SPM) (see the part of Baseline and [38]). …”
Section: Network Formation and Metricsmentioning
confidence: 99%
“…Our work naturally embeds into this context, since the scholar citation network we use is an instance of a temporal network in which citation links are timestamped with the time of publication of the citing paper. Static ranking methods applied to dynamic and evolving networks have been found to exhibit important shortcomings [Liao et al, 2017], consequently a variety of dedicated methods have been put forward.…”
Section: Related Workmentioning
confidence: 99%
“…The presence of growth challenges traditional network analysis [6,7] and makes it essential to develop and validate time-aware methods to achieve a solid understanding of the structure of these systems [8]. In particular, extensive research has shown that the inclusion of temporal information into network analysis has a dramatic impact on long-studied problems such as community detection [9][10][11], node ranking [11][12][13], dynamics control [14], and spreading phenomena [15][16][17].…”
Section: Introductionmentioning
confidence: 99%